Kematangan Emosi dan Religiusitas Terhadap Kecenderungan Agresi Pada Siswa - Putri Maharani; Hermien Laksmiwati (Jurnal Psikologi Teori dan Terapan, 2017)
The purpose of this research was to determine the correlation between emotional maturity and religiosity with aggressive tendency among students. This research used quantitative research method. The population was  grade 10  students of  SMA "X" Mojokerto (120 students). Instruments used were the scales of emotional maturity, religiosity, and aggressive tendency. Pearson product moment was used to find a partial relationship between variables, while multiple linear regression was used to find the relationships of emotional maturity (X1) and religiosity (X2) to aggressive tendency (Y) simultaneously. The result of the analysis between X1 and Y shows correlation coefficient of -0.717, while  correlation coefficient  between X2 and Y was -0.601. The results also show that the partial relationship between X1 with Y and X2 with Y is at a high level. The results of multiple linear regression analysis shows that the correlation coefficient of X1 and X2 with Y was 0.613. The result means that the contribution of emotional maturity and religiosity variables on aggressive tendency is 61.3%. The negative coefficient values in emotional maturity and religiosity variables indicate that the higher emotional maturity and religiosity will result in the lower aggressive tendency. In contrast, when emotional maturity and religiosity is lower, then aggressive behavior tendency will be higher. Abstrak: Penelitian ini bertujuan untuk menguji hubungan antara kematanagan emosi dan reigiusitas dengan kecenderungan perilaku agresi pada siswa. Penelitian ini menggunakan metode kuantitatif. Populasinya adalah siswa kelas X SMA œX Kota Mojokerto yang berjumlah 120 siswa. Instrumen yang digunakan adalah skala kematangan emosi, religiusitas, dan kecenderungan agresi. Teknik analisa data menggunakan product moment untuk mencari hubungan secara parsial, dan analisis regresi linier berganda  untuk mencari hubungan secara simultan. Hasil analisis antara kematangan emosi dengan kecenderungan agresi menunjukkan koefisien korelasi-717, dan sebesar -601 antara religiusitas dengan kecenderungan agresi. Hasil tersebut menunjukkan bahwa hubungan parsial antara X1 dengan Y dan X2 dengan Y berada pada tingkat tinggi.  Hasil analisis data secara bersama-sama variabel X1 dan X2 dengan Y menunjukkan koefisien korelasi sebesar 0,613 artinya kontribusi variabel kematangan emosi dan religiusitas secara bersama-sama terhadap kecenderungan perilaku agresi adalah sebesar 61,3%. Nilai koefisien pada variabel kematangan emosi dan religiusitas adalah negatif. Artinya semakin tinggi kematangan emosi dan religiusitas maka semakin rendah kecenderungan agresi siswa. Sebaliknya, kematangan emosi dan religiusitas rendah terkait dengan kecenderungan agresi tinggi.